Bibliometric analysis for process capability research. Issue 4 (4th July 2019) - Ahmad, Shafiq; Alatefi, Moath; Alkahtani, Mohammad; Anwar, Saqib; Sharaf, Mohamed; Abdollahian, Mali
Abstract: Bibliometric research focuses on the analysis of the bibliographic indicators quantitatively. It is a useful way for classifying information according to different variables, including journals, institutions and countries. This paper presents a general overview of research conducted in the field of process capability using bibliometric indicators. The main advantage of the current study is that the bibliometric indicators provide a broad picture and identify some of the most influential research conducted in the area of process capability. The analysis is divided into key sections focused on relevant journals, research papers, authors, institutions and countries. Web of Science (WOS) databases is the source of data for carrying out this bibliometric analysis. The study reveals that W.L. Pearn and C.W. Wu. are the two most influential authors in process capability research. On the other hand, Journal of Quality Technology, and Quality and Reliability Engineering International are the two most influential journals for publishing process capability researches. Furthermore, Taiwan is found to be the most influential country, followed by the U.S.A. in the process capability research.